Konsep Pendidikan Al-Qur’an Dalam Membentuk Masyarakat Islami (Al-Mujtama’ Al-Islami): (Tafsir Al-Qur’an Surat an-Nahl ayat 112) - Rahma, Farida Nur; Hidayat, Tatang; Kusumah, Mada Wijaya; Hafidhuddin, Didin; Al-Hamat, Anung (ZAD Al-Mufassirin, 2023)
Indonesia as a country with the largest Muslim population in the world does not necessarily make it an Islamic society (Al-Mujtama' al Islami). This is because the living system that oversees it is not an Islamic system or rule. Secularism and capitalism are still the spirit in making various laws and regulations. So that the feelings and thoughts that are born and appear are liberal feelings and thoughts. The purpose of this study is to find the concept of Al-Quran education Surah An-Nahl verse 112 in shaping Islamic society. With the literature study method, researchers found the foundation of this education is Islam. The goal is to form a society that obeys, hastens and accepts Islamic law in total. So that the security and prosperity of Islam are bestowed by Allah for them. This goal must be supported by the application of Islamic law by the state, unity based on Islamic aqidah, enforcement of amar ma'ruf nahyi munkar and legal sanctions that make deterrent and atone for sins.